Implikasi Kebijakan atas Terbitnya Travel & Tourism Development Index 2021 Terhadap Upaya Peningkatan Daya Saing Kepariwisataan Indonesia di Pasar Global - Maulana, Addin; Oktaviyanti, Dini; Wahyuni, Dwi; Sasono, Norman; Sakti, Guntur (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
Changes in the framework, methodology, and indicators used by the World Economic Forum (WEF) in measuring and ranking the competitiveness of world tourism through the Travel and Tourism Development Index (TTDI) have implications for Indonesian government policies in achieving the target of tourism competitiveness rankings. By using a qualitative descriptive approach, and documentation study techniques in data collection, this policy study aims to provide an overview of the policy implications of the issuance of the 2021 TTDI. The legal umbrella for increasing tourism competitiveness consists of laws, presidential regulations, government regulations, and ministerial regulations. In 2019 Indonesia's Travel and Tourism Competitiveness Index (TTCI) ranking was 40, but after conversion using the TTDI framework, methodology, and indicators, the rank dropped to 44. Indonesia's TTDI ranking in the 2021 edition is 32, meaning an increase of 12. The change from TTCI to TTDI has implications for adjustment of the target performance indicators related to tourism competitiveness written in the president's regulation and the regulation of the minister of tourism and creative economy. This change also causes ministries/agencies to remap supporting indicators that potentially impact adjusting the legal umbrella related to cross-sectoral coordination of tourism implementation in Indonesia.